Intersection Between Modern Technologies and Halal Tourism - Md Siddique E Azam; Betania Kartika Muflih; M Ashraf Al Haq (Universiti Sains Islam Malaysia, 2024)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 1 Page (16-31)